Identification and prediction of patients eligible for augmented rehabilitation in emergency gastrointestinal surgery (RAUCisable): A protocol for a single-centre, retrospective, observational study - Émilien Arnaud; Gilles Dequen; Émilie Chivé; Delphine Lignier; William Gacquer; Momar Diouf; Thibaut Balcaen; Daniel Aiham Ghazali; Jean-Marc Regimbeau (PLoS ONE, 2026)
Introduction Conditions requiring emergency gastrointestinal surgery pose substantial challenges to healthcare systems and patient outcomes. For emergency gastrointestinal surgery, the mortality rate is higher than after other types of surgery, and 30-day readmission rates can exceed 30%. Unlike elective surgery (for which the application of enhanced recovery after surgery (ERAS) procedures has led to demonstrably better recovery), emergency surgery patients are still managed in an ad hoc manner. The Réhabilitation Augmentée pour les Urgences Chirurgicales (RAUC) multi-faceted research program has been designed to transform the care of patients undergoing emergency gastrointestinal surgery [7]. The ancillary RAUCisable study will develop a classification model that can automatically flag up RAUC-eligible patients early in their visit to the emergency department (ED). The study’s secondary objectives include the identification of key features and the prediction of time to surgery. Method RAUCisable is single-centre, retrospective, observational cohort study of electronic health records in the ED and digestive surgery department at Amiens-Picardie University Hospital (Amiens, France). All adult patients having attended the ED between January 1st, 2021, and December 31st, 2024, will be considered for inclusion. The primary classification outcome is eligibility for the RAUC pathway. Expected results We expect to identify ~2,400 RAUC-eligible patients from among ~250,000–300,000 ED visits over a 4-year period. These patients are likely to be significantly older than non-surgical ED patients (e.g., more over-65s), with a higher proportion of acute abdominal conditions (e.g., ~ 24% with appendicitis, ~ 13% with bowel obstruction, ~ 10% with peritonitis, etc.), and greater disease acuity on triage. Discussion The RAUCisable study’s findings will directly guide a concomitant, prospective, controlled study (RAUC-AMIENS) of the augmented recovery pathway, including ERAS elements and remote monitoring. Conclusion The RAUCisable study is a pivotal step toward digitally enhanced emergency surgical care. By learning from past data, we are seeking to improve the future management of emergency surgery patients through timely identification and targeted care pathways. This protocol article details our methodological approach for ensuring rigor and reproducibility. Trial registration NCT07037719